Pathologic complete response to chemoimmunotherapy of an advanced gastric cancer patient with high PD-L1 expression, dMMR, and unique gut microbiota composition: A case report - Jiang, Hongpeng; Wang, Junyun; Deng, Wei (Frontiers in Oncology, 2023)
Background Advanced gastric cancer (AGC) is a malignant disease with limited therapeutic options and a poor prognosis. Recently, immune checkpoint inhibitors (ICIs), represented by inhibitors of programmed cell death 1 (PD-1)/programmed death-ligand 1 (PD-L1), have emerged as a potential gastric cancer (GC) therapy. Case presentation This case study aimed to reveal the tumor response to neoadjuvant chemotherapy combined with camrelizumab in a patient with AGC based on the characteristics of the clinical pathology, genomics variation, and gut microbiome. Samples from a 59-year-old male patient diagnosed with locally advanced unresectable GC (cT4bN2M0, high grade) presenting PD-L1-positive, deficient mismatch repair (dMMR), and highly specific gut microbiota enrichment were subjected to target region sequencing, metagenomic sequencing, and immunohistochemistry staining. The patient received neoadjuvant therapy, including camrelizumab, apatinib, S-1, and abraxane, which eventually promoted dramatic tumor shrinkage without serious adverse effects and allowed subsequent radical gastrectomy and lymphadenectomy. Finally, the patient achieved pathologic complete response (pCR), and the recurrence-free survival time was 19 months at the last follow-up in April 2021. Conclusions The patient with PD-L1-positive, dMMR, and a highly specific gut microbiota enrichment exhibited a pCR to neoadjuvant chemoimmunotherapy.